Living Constitution in Islamic Constitutional Law: A Comparative Study of Gorontalo Customary Constitutional Law in Majority and Minority Enclave Contexts - Moonti, Roy Marthen; Akili, Rustam Hs.; Kadir, Yusrianto; Bunga, Marten; Halfaoui, Amro (Jurnal Ilmiah Al-Syir'ah, 2025)
This study analyzes the operationalization of Gorontalo customary law as a living constitution within the framework of Islamic Constitutional Law in two different demographic contexts: a Muslim majority society in Gorontalo Province (98.1%) and a Muslim minority enclave in Ternate Tanjung Sub-District, Manado City (86.7% at the sub-district level and 31.9% at the city level). Using a socio-legal comparative research approach, this study examines how adat-Islamic constitutional norms function, adapt, and obtain legitimacy within different constitutional structures. Data were collected through in-depth interviews with four key informants, comprising two Gorontalo customary leaders and two Manado community leaders. The findings demonstrate that the principle "Adati hula-hulaa to Syara’, Syara’ hula-hulaa to Qur’ani" functions as the basic norm (substantive grundnorm) of Gorontalo Islamic Constitutional Law that remains stable across demographic contexts. However, the constitutional operationalization mechanism undergoes transformation. In the Muslim majority context, customary law operates formally through the Buwatulo Taulongo institution, which enjoys dual legitimacy, both customary and state, thereby forming a local living constitutional order. Conversely, in the Muslim minority context, customary law operates flexibly-informally through family deliberation and ad-hoc mediation by sub-district officials, imams, and the Office of Religious Affairs. This transformation is not degradation, but rather constitutional rearticulation aligned with the principles of Fiqh al-Aqalliyyat: yusr, maslahah mursalah, muwatanah, and tadarruj. This research develops a layered Living Fiqh al-Aqalliyyat model from an Islamic Constitutional Law perspective, expanding the concept of a living constitution from temporal adaptation to demographic adaptation, particularly in the context of domestic Muslim minorities in Eastern Indonesia.